Is Splenectomy still the best treatment for Autoimmune hemolytic anemia - Chomicz, Malwina; Puszkarz, Aleksandra; Łukaszewska, Anna; Łukaszewska, Ewa; Bąk, Mateusz; Guzik, Natalia; Bik, Tomasz; Gaj, Łukasz; Drozdowska, Katarzyna; Łukaszewska-Stanik, Katarzyna (Journal of Education, Health and Sport, 2023)
Introduction: Autoimmune hemolytic anemia (AIHA) is an acquired, heterogeneous group of diseases that includes AIHA with warm type antibodies, cold agglutinin disease (CAD), mixed type AIHA, paroxysmal cold hemoglobinuria, and atypical AIHA. Currently CAD is defined as chronic, clonal lymphoproliferative disease, while presence of cold agglutinin in gastrointestinal tract is known as cold agglutinin syndrome. AIHA is mediated by autoantibodies against red blood cells (RBCs), these antibodies cause premature destruction of erythrocytes. The pathogenesis of AIHA is complex and still not yet fully understood. Aim of study: The purpose of the study was to review the literature on the treatment options for Autoimmune Hemolytic Anemia Materials and methods: A systemic review was conducted using PubMed, ScienceDirect, Google Scholar databases. The search strategy was based on following terms: Aiha, splenectomy autoimmune anemia, aiha treatment, Results and Conclusions: Based on the review of the medical literature, we believe that Splenectomy is no longer the most effective method of treating any type of AIHA and the Rituximab treatment presented by us seems to be safer and definitely less burdensome for the patient. Of course, splenectomy is still used in AIHA - but nowadays it is more limited due to the very high effectiveness of the described non-surgical treatment